STRATEGI PENINGKATAN KUALITAS DATA PERTANAHAN UNTUK MEWUJUDKAN DESA LENGKAP - Arfiana, Mariska Widya; Utami, Westi (Jurnal Spasial, 2024)
Improving the quality of land data is very necessary so that all land parcels are mapped and valid so that a complete village mapping is arranged. This study aims to describe the implementation strategy and evaluate the improvement of the quality of land data in order to realize a Complete Village based on man, money, machine, material, and method. The research was conducted through a mix of quantitative and qualitative methods. The results of the study show that the Land Office of Ponorogo Regency applies a strategy by optimizing man, money, machine, material, and method, so that all villages meet the requirements to generate a Complete Village Value (NDL) of 100. ) the number of officers is not sufficient, b) the budget allocation is limited so that some achievements cannot be disbursed, c) the equipment used has not been utilized optimally, d) the types of documents are quite complete but there is still information that has not been recorded in full, e) setting targets for K4 activities not well planned. Measurement and mapping carried out in one village.